Cover Picture: The Enantioselective Total Synthesis of Bisquinolizidine Alkaloids: A Modular "Inside‐Out" Approach (Angew. Chem. Int. Ed. 9/2018). Issue 9 (5th February 2018) - Scharnagel, Dagmar; Goller, Jessica; Deibl, Nicklas; Milius, Wolfgang; Breuning, Matthias
Abstract : A modular "inside‐out" approach to 21 natural bisquinolizidine alkaloids, among them more than ten first enantioselective total syntheses, is reported by M. Breuning et al. in their Communication onpage 2432 ff. Key was the successful preparation of both enantiomers of C 2 ‐symmetric 2, 6‐dioxobispidine by desymmetrization and the successive α, N ‐annulation of a 2‐pyridone and endo ‐ or exo ‐fused piperidines to the chiral core building block.